Distribution of Pathogens in Elderly Chinese Patients With Pneumonia: A Systematic Review and Meta-Analysis - Chen, Luming; Huang, Hongqiang; Chen, Xiaolin (Frontiers in Medicine, 2021)
Background: To summarize the distribution of pathogenic bacteria in elderly Chinese patients with pneumonia and provide guidance for the clinical application of antibiotics. Methods: The electronic databases of PubMed, Embase, Cochrane library, and China National Knowledge Infrastructure were searched. The primary outcomes included the prevalence of gram-positive cocci, gram-negative bacilli, and fungus. The summary prevalence and 95% confidence interval (CI) were calculated using the random-effects model. Results: A total of 17 retrospective studies reporting a total of 5,729 elderly patients with pneumonia were selected for final analysis. The summary prevalence of gram-positive cocci was 25% (95% CI: 20–30%; p < 0.001), whereas the prevalence of gram-negative bacilli was 56% (95% CI: 46–67%; p < 0.001). Moreover, the pooled prevalence of fungus in elderly patients with pneumonia was 11% (95% CI: 8–14%; p < 0.001). The most common gram-positive cocci were Staphylococcus aureus (ES: 8%; 95% CI: 6–11%; p <0.001), Streptococcus hemolyticus (ES: 7%; 95% CI: 6–8%; p < 0.001), and Streptococcus pneumoniae (ES: 5%; 95% CI: 3–7%; p < 0.001). Pseudomonas aeruginosa (ES: 18%; 95% CI: 14–22%; p <0.001) and Klebsiella pneumoniae (ES: 14%; 95% CI: 11–18%; p <0.001) were most common gram-negative bacilli. Furthermore, the pooled prevalence of Candida albicans in elderly patients with pneumonia was 6% (95% CI: 5–8%; p < 0.001). Conclusions: The findings demonstrated the comprehensive distribution of pathogenic bacteria in elderly Chinese patients with pneumonia, which could guide further antibiotic therapies.